Novel point-of-care biomarkers of the dry anophthalmic socket syndrome: tear film osmolarity and matrix metalloproteinase 9 immunoassay - Rokohl, Alexander C.; Wall, Katharina; Trester, Marc; Wawer Matos, Philomena A.; Guo, Yongwei; Adler, Werner; Pine, Keith R.; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: To compare tear film osmolarity (TFO) values and matrix metalloproteinase 9 (MMP-9) levels between anophthalmic sockets and healthy fellow eyes and to assess the use of the MMP-9 and TFO as objective biomarkers for the dry anophthalmic socket syndrome (DASS). Methods: In this prospective single-center study, the anophthalmic sockets and healthy fellow eyes of 98 unilateral anophthalmic patients were assessed using the ocular surface disease index (OSDI) questionnaire, InflammaDry® MMP-9 point-of-care immunoassay, TFO with TearLab™ Osmolarity System, and clinical conjunctival inflammation. MMP-9 concentration and conjunctival inflammation were graded semi-quantitatively. Differences between anophthalmic sockets and the healthy fellow eyes for OSDI scores, MMP-9, TFO values, clinical conjunctival inflammation, and eyelid abnormalities as well as the correlation between these factors and demographic data were evaluated. Results: Patients had significantly higher OSDI, MMP-9, and TFO values, as well as higher conjunctival inflammation on the anophthalmic side, compared to the healthy side (p ≤ 0.002, respectively). For anophthalmic sockets, there was a significant positive correlation between OSDI scores and TFO values (p = 0.007), between the grade of posterior blepharitis and TFO values (p = 0.026), and between the conjunctival inflammation and MMP-9 values (p < 0.001), as well as between MMP-9 levels and time since eye loss (p = 0.004). Conclusions: Measuring MMP-9 and TFO may be helpful tools as efficient, quantifiable biomarkers, disease course parameters, or predictors for treatment response in the clinical management of patients with DASS or future therapy studies. Ophthalmologists should consider the updated diagnosis criteria including TFO and the definition for DASS proposed in this study.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Anophthalmic socket surface inflammation; Conjunctival inflammation; Dry anophthalmic socket syndrome; Enucleation; Evisceration; Matrix metalloproteinase 9; Tear film osmolarity